Association between the C-reactive protein/albumin ratio and mortality in older Japanese patients with dysphagia - Guo, Chunhong; Zheng, Pingping; Chen, Shiyang; Wei, Lin; Fu, Xiuzhen; Fu, Youyuan; Hu, Tianhong; Chen, Shaohua (Frontiers in Nutrition, 2024)
Background: C-reactive protein-to-albumin ratio (CRP/ALB) has been proven to represent a biomarker for predicting prognosis in many groups of patients with severe diseases. However, few studies have investigated the association between CRP/ALB and mortality in Japan older people with dysphagia patients. Objective：This retrospective cohort study aimed to assess the prognostic value of C-reactive protein/albumin ratio (CAR) in older Japanese patients with dysphagia. Methods：We analyzed data from 253 patients diagnosed with dysphagia at a single center between January 2014 and January 2017. Cox regression analysis was used to compare the mortality rates across the CAR tertiles. Subgroup analyses were conducted, and Kaplan–Meier curves were used to determine the median survival times. Results: The study included 154 female and 99 male patients, with a median age of 83 years. After adjusting for all covariates, the multivariable Cox regression analysis revealed a significant association between increasing CAR (HR=1.19, 95% CI: 1.03–1.37, P=0.022) and the risk of mortality. Compared to the reference group T1 (＜0.149), the adjusted hazard ratios for T2 (0.149–0.815) and T3 (≥0.815) were 1.75 (95% CI: 1.07–2.87, P=0.027) and 2.15 (95% CI: 1.34–3.46, P=0.002), respectively. Kaplan–Meier curves indicated median survival times of 864, 371, and 223 days for T1, T2, and T3, respectively. Conclusion：The C-reactive protein/albumin ratio was positively related to mortality in Japan older people with dysphagia patients. There was no interaction for the subgroup analysis. The result was stable.